The effect of Povidone and Fusidic acid ointments on limb wounds of the horses (Journal of Hama University, 2019)
The objective of this study is to determine the effect of the application of Povidone ointment 10% , compared with the ointment Fusidic acid 2% on healing  limbs wounds of the horses. The study is includes  (48)  horses with limb wounds injury. The limb wounds in horses have been classified according to  the  period of time that passed on the wounds (recent or old), where the  injury proportion of recent wounds(75%), while old wounds with ( 25%) . The  horses  with limb wounds are divided  into  two groups, randomly, the ages from two to eighteen years and their weights between (350 and 175) Kg : The first group: (n=24) are  treated  by using the ointment of  Povidone  10% topically on the wounds. The  second group: (n=24) are treated  by  using the ointment of   Fusidic  acid  2%  topically on the wounds. It has  been  concluded that this study has shown that healing of  limb wounds in horses treated by using  the ointment  of  Fusidic acid (2%)  was better than using  Povidone 10% , in terms of speed of wound  contraction , Where the average number of days for healing by Fusidic acid  is (±72) and the average number of days of healing  by Povidone  is (±83),in terms  of  the constitution of prominent scar and also in terms of the average number of times of eradication of excessive granulation tissue.